Educational leadership connecting the world - Sokol, Yevgen I.; Mukuni, Joseph; Lapuzina, Olena Mykolayivna (National technical university "Kharkov politechnical institute", 2024)
Theoretical, methodical and practical issues of the ethics of leadership of a modern specialist, its nature, essence and basic principles are considered. The manual contains brief information that allows students to get a general idea of leadership, information about methods of forming leadership qualities of teachers and students, information about startups, as an important component of the future specialist-leader. The manual is intended for students of all majors studying the "Leadership" course, and may also be useful for teachers of psychological, pedagogical and management disciplines.
Keywords: educational manual; educational leadership; ethics of leadership; modern specialist; methods of forming leadership qualities; leadership